Joaquín de Fiore and Franciscan eschatology in the cathedral of Ayaviri - Lara, Jaime (2011)
It has long been recognized that Joachim of Fiore (+1202), the Calabrian abbot, prophet and artist, had a profound influence on the mendicant orders, especially among the Franciscans, who recognized their holy founder in his eschatological prophecies. Andean Franciscan art -such as the Ayaviri canvases- used Joaquinist references and influenced the portrait of the abbot in paintings that show a flying Saint Francis, iconography that has its origin among the indigenous artists of Cusco. There is evidence that the Andean people saw and understood the winged saint, with his utopian messages, as a shaman and bird-man. Anthropologists have found the memory of the three Joachim ages of the Father, Son, and Holy Spirit in various Andean communities today. This research suggests that Joachim de Fiore was better known in the colonial world than in the medieval Europe in which he lived, and that the visual arts had much to do with this fact.